Original paperInsulin resistance in severe acne vulgaris - Emiroğlu, Nazan; Cengiz, Fatma Pelin; Kemeriz, Funda (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction: Acne vulgaris is a pilosebaceous gland disease that usually affects people from puberty to young adulthood. It is seen especially on the face, neck, trunk and arms. Its severity differs from patient to patient and its pathogenesis is multifactorial. The main pathogenic factors of acne are high sebaceous gland secretion, follicular hyperproliferation, high androgen effects, propionibacterium acnes colonization and inflammation. Diet is always thought a probable reason for acne and many studies are done about acne and diet. Aim: To determine the effect of insulin resistance in severe acne vulgaris. Material and methods: Two hundred and forty-three acne vulgaris patients and 156 healthy controls were enrolled into the study. The blood levels of insulin and glucose were measured. Homeostasis Model Assessment (HOMA) Index was calculated. The values were compared with the control group. Results: All of the patients were in the severe acne group according to their scores on the global acne scoring scale. While fasting blood glucose levels were not different between the groups (p > 0.05, 82.91 ±9.76 vs. 80.26 ±8.33), the fasting insulin levels were significantly higher in the patient group than in the control group (p < 0.001, 14.01 ±11.94 vs. 9.12 ±3.53). Additionally, there was a highly significant difference between the patient and control groups in terms of HOMA values (p < 0.001, 2.87 ±2.56 vs. 1.63 ±0.65). Conclusions : These results suggest that insulin resistance may have a role in the pathogenesis of acne.